An integrated collaborative approach for FM-sydney opera house FM exemplar - Morris, J.; Ballesty, S.; Ding, L.; Drogemuller, R.; Mitchell, J.; Schevers, H.; Leifer, D.; Schwede, D.; Wu, Jeremy; Henrikson, J.; Akhurst, P.; Spink, G. (2006)
This paper presents an integrated collaborative approach for facilities management (FM), which utilises Sydney Opera House as an exemplar case study. The project has three (3) research streams, Digital Modelling, Services Procurement and Benchmarking, which are considered individually and as an integrated whole. The project aims to achieve innovative FM strategies and models that will potentially be of benefit to the Australian facilities management industry. The Digital Modelling theme aims to develop building information modelling for facilities management and investigates the potential of state-of-the-art information systems to enable a future integrated platform to support facility management collaborative activities and processes. The Procurement theme focuses on FM service procurement, especially for outsourcing. Procurement methods and a multi-criteria assessment approach for supporting decision making have been examined. The Benchmarking theme focuses on the maintenance of iconic assets, specifically performing art centres and facilities with similar functionalities. Critical success factors in the functional areas of asset maintenance are identified against organisational objectives of Sydney Opera House and key performance indicators developed. Separately, the suggested collaboration between Procurement and Benchmarking includes potential for the linking of key performance indicators to support Sydney Opera House's Total Asset Management (TAM) strategies and corporate objectives.